Implementasi Digital Technologies dalam Sistem Akuntansi UMKM: Penguatan Efisiensi Operasional dan Akuntabilitas Keuangan - Anisa, Anisa; Masyhuri, Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, yet weaknesses in accounting systems continue to hinder financial management quality and business sustainability. This study analyzes the role of digital technologies in improving the efficiency and transparency of accounting systems within MSMEs through a non-empirical library research approach. The findings indicate that digital technologies, including cloud accounting, mobile accounting applications, digital payment integration, and blockchain-based accounting systems, contribute significantly to improving financial data accuracy, accountability, auditability, and governance quality in MSMEs. However, implementation remains constrained by limited digital literacy, inadequate infrastructure, cybersecurity risks, organizational resistance, and uneven technological readiness. Sustainable digital accounting transformation requires collaborative governance and continuous institutional support to develop resilient MSME financial ecosystems.